Inclusive and Sustainable Conservation Partnerships: An applied approach for improving Peru’s Market- based-mechanism strategies with Indigenous Communities - (:unkn) unknown (My University, 2026)
SoW Dr. Deborah Delgado will assist in implementing and overseeing field research in Peru, including contributing to study design, data collection, field worker oversight, and data analysis and synthesis. PUCP has assisted in preparing a budget justificat